Introduction of Gambhir Thoracostomy Tube forceps and analysis of 100 cases of thoracostomy tube drainage - Rajbhandari, G L (Medical Journal of Shree Birendra Hospital, 2006)
Introduction of Gambhir Thoracostomy Tube forceps and analysis of 100 cases of thoracostomy tube drainage